How does educational inequality affect residents’ subjective well-being?—Evidence from China - Lin, Difeng; Liu, Zeyun (Frontiers in Psychology, 2024)
In the context of promoting educational equity and improving welfare, exploring ways to further enhance residents' subjective well-being from the perspective of educational equity holds significant practical importance.This study uses the educational Gini coefficient to measure the educational inequality index across different provinces and cities, and matches it with data from the China Family Panel Studies (CFPS) to investigate the relationship between educational inequality and residents' subjective well-being. The research findings reveal a significant negative correlation between educational inequality and residents' well-being, with observed heterogeneity. Specifically, educational inequality has a greater negative impact on groups with lower levels of wellbeing, rural areas, and the central and western regions of China. Mechanism analysis confirms the income distribution effect and economic growth effect of educational inequality. Therefore, increasing attention to the issue of educational equity and understanding the well-being effects of educational inequality are of great significance for the Chinese government in improving residents' welfare in the new era.